Lietuva Vidurio ir Rytų Europoje XVI-XVIII amžiuje: „feodalinė reakcija" ar periferinis kapitalizmas? - Žiemelis, Darius (Lietuvos istorijos studijos, 2006)
The subject of the article is the historiography analyzing the development of the socio-economic order of Central and Eastern Europe in the 16th-18th centuries and specifically two competing theoretical approaches: the Marxist concept emphasizing the role of inner causes and of the capitalist world system (CWS) stressing external causes. The problem that the article is concerned with is the nature of the second serfdom in Central and Eastern Europe in the 16th-18th centuries: was this refeudalization in the Marxist sense, or peripheral capitalism in the CWS context? In Marxist historiography (beginning with Friedrich Engels), the concept of the second serfdom means the process of refeudalization. The neo-Marxist CWS theory of I. Wallerstein, applying an approach, suggests looking at the phenomenon of the second serfdom from the global perspective, describing it as an expression of peripheral capitalism in Central and Eastern Europe. The article compares the explanation I. Wallerstein provides of the second serfdom in Central and Eastern Europe (especially in the Polish-Lithuanian state) with earlier interpretations of it (especially in Marxist historiography) and attempts to provide an answer that will bring greater focus to later investigations by establishing greater explanatory power of the comparative conceptions.